Regulatory Experience Assessing the Carcinogenic Potential of a Monoclonal Antibody Inhibiting PCSK9, Bococizumab, Including a 2-Year Carcinogenicity Study in Rats. (September 2022) - Buetow, Bernard S.; Cappon, Gregg D; Aschenbrenner, Laura M.; Updyke, Lawrence; Torti, Vince R.; Evans, Mark; Dalton, Shana R.; Bailey, Steven; Bowman, Christopher J.
Bococizumab is an anti-PCSK9 monoclonal antibody that was intended for the treatment of hypercholesterolemia. After reviewing the 6-month rat toxicity study data, in which there was a low spontaneous tumor incidence, unrelated to bococizumab administration, the U.S. FDA granted a carcinogenicity waiver request based on a weight-of-evidence assessment of low carcinogenic risk. Subsequently, after reviewing 6-month rat toxicity study data from another anti-PCSK9 antibody, RN317, with a similar low tumor incidence (unrelated to RN317), the U.S. FDA rescinded the bococizumab carcinogenicity study waiver and requested a full 2-year rat carcinogenicity study be conducted. The resulting 2-year carcinogenicity study demonstrated no bococizumab-related increase in tumors, confirming the weight-of-evidence evaluation and alleviating concerns regarding the carcinogenic potential. Here we report the scientific and regulatory background that led to the request for a rat carcinogenicity study, the feedback on the design of the carcinogenicity study, and the results from this study which affirmed the original weight-of-evidence assessment of low carcinogenic risk.